اشتہاری عبارت: تعریف، اجزا اور اسالیب سے متعلق اسلامی نقطۂ نظرAdvertisement Text: An Islamic Perspective on its Definition, Parts and Styles (Al-Qamar, 2022)
The rapid growth of technology is demanding Muslims to think about the Islamic Rulings of modern issues, because it is an established fact and required from Muslims to act according to the ruling of Islam in every walk of life. One of the novel issues is an Advertisement and its different aspects. This article aims to discover advertisement text and its various parts and styles. Further it discusses how the text alters its shape with the medium of the advertisement. If it is a print media, its text will be readable, and sequence of words will be aligned with it. if it is a radio, its text will be audio able, and words will be chosen appropriately and if it is a TV, video or cinema, the statements and visual styles will be selected suitably. Firstly, the definition of Advertisement Text and parts of that text have been stated. Afterwards, several Advertisement Styles and types of one of the styles have been mentioned. Along with them Islamic point of view has been written. The conclusion summarizes the article in the end and comprises the answer to the research question that the Islamic teachings clarify rulings of the Advertisement text, its parts, styles, and gifts provided for attracting customers. The article winds up the discussion with a suggestion of implementing Islamic rules in the Advertisement text, its parts, and styles.
Keywords: Advertisement; Islam; Text; Style